IMPLEMENTATION OF AN ELECTRONIC HOSPITAL INFORMATION SYSTEM IN A DEVELOPING COUNTRY; A CASE STUDY OF FED.MED. CENTER OWERRI, NIGERIA. - Agbasonu, Valerian C.; Bethram , Amanze (Journal of Medical Care Research and Review, 2021)
Concerned by the overwhelming increase in the population of patients attending our hospitals for medical attention and the problems associated with the sluggish, unreliable and insecure manual (paper work) method of keeping record of patient’s information; the need for an electronic information system which makes it easier ,more reliable and more economical to keep and retrieve a patient,s information as at and when needed with high degree of speed, and precision has become inevitable in our medical system .Manual method of record keeping which has been in use in the hospital where this research was carried out was observed to be inadequate, often inaccurate and lacks flexibility. Personal interview carried out on both patients and staffs of the hospital showed that more than 70% of the respondents prefered an electronic system of information storage and retrieval that will reduce the time and energy wasted in sorting out files from heaps of files from racks when a patient is to be attended to. Due to this obvious problems, the researcher was motivated to develop a software that will handle this problem